McGregor Flap in Reconstruction of Lower and Upper Eyelid Defects - Mir Yasir; Hillal Ahmad Bhat; Altaf Rasool; Mir Mohsin; Umar Farooq Baba; Haroon Rashid Zargar; Sheikh Adil Bashir; Adil Hafeez Wani (Archives of Medicine and Health Sciences)
Background and Aim: Reconstruction of the eyelid is a surgical challenge, keeping in view both the cosmetic and functional importance of the eyelid. Here, we are describing our experience with the McGregor flap technique for the closure of full-thickness eyelid defects. Materials and Methods: This study was conducted prospectively from August 2015 to July 2018 in one of the tertiary care hospitals in North India. This study consisted of a total of 15 patients treated for eyelid defects following the excision of neoplastic disease of the lids. The final result of the reconstructive procedure was recorded at 6 months postoperatively. Results: Most of our patients were above the age of 50 (11 patients) and comprised predominantly females (9 patients). All the defects were reconstructed by the McGregor flap technique. We had excellent functional results in 13 (86.66%) patients, a good result in 1 (6.66%) patient, and an acceptable result in another (6.66%) patient. In terms of cosmesis, excellent results were found in 13 (86.66%) patients and acceptable in the remaining 2 (15.38%) patients. Conclusion: The McGregor flap for eyelid defect reconstruction is a reliable, good, and easy technique for reconstructing full-thickness eyelid defects involving up to 2/3rd of the horizontal length of eyelids. The technique can be successfully used for upper eyelid reconstruction with excellent functional and cosmetic results.